The ethnography of rhythm : orality and its technologies - Saussy, Haun, 1960- (Verbal arts--studies in poetics., 2016)
"A history of the concept of orality (that is, the creation and transmission of literary works without the use of writing), this book shows awareness of this medium emerging from the encounter of many literary and scientific developments (romanticism, post-symbolism, structuralism; physiology, psychology, the study of expression, anthropology; phonography, cinema)"--